2024
DOI: 10.1021/acs.jcim.4c00079
|View full text |Cite
|
Sign up to set email alerts
|

Probing Enzymatic PET Degradation: Molecular Dynamics Analysis of Cutinase Adsorption and Stability

Mehdi Sahihi,
Pierre Fayon,
Lionel Nauton
et al.

Abstract: Understanding the mechanisms influencing poly(ethylene terephthalate) (PET) biodegradation is crucial for developing innovative strategies to accelerate the breakdown of this persistent plastic. In this study, we employed all-atom molecular dynamics simulation to investigate the adsorption process of the LCC-ICCG cutinase enzyme onto the PET surface. Our results revealed that hydrophobic, π−π, and H bond interactions, specifically involving aliphatic, aromatic, and polar uncharged amino acids, were the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recently, Sahihi and collaborators ( 71 ) provided relevant data on the molecular dynamics between a PETase and PET. It was reported that hydrophobic interactions were important for enzymatic adsorption toward PET ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sahihi and collaborators ( 71 ) provided relevant data on the molecular dynamics between a PETase and PET. It was reported that hydrophobic interactions were important for enzymatic adsorption toward PET ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sahihi and collaborators ( 71 ) provided relevant data on the molecular dynamics between a PETase and PET. It was reported that hydrophobic interactions were important for enzymatic adsorption toward PET ( 71 ). In our work, we observed a similar trend with SusD, revealed by the predicted presence of hydrophobic pockets within the proteins’ surface.…”
Section: Resultsmentioning
confidence: 99%